Long-term seizure outcome with the surgically remediable syndrome of frontal lobe epilepsy associated with superior frontal sulcus-related dysplasia - Xu, Yan; Hu, Wen-Han; Shao, Xiao-Qiu; Ma, Yan-Shan; Lou, Lin; Zhang, Kai; Zhang, Jian-Guo (Frontiers in Neurology, 2023)
Objective: To assess the long-term outcome of the surgically remediable syndrome of frontal lobe epilepsy (FLE) associated with superior frontal sulcus (SFS) related dysplasia. Methods: We retrospectively reviewed the medical charts and surgical features of 31 patients with drug-resistant frontal lobe epilepsy in our centers between 2016 and 2018. All patients underwent surgical resection. According to the epileptogenic zone (EZ) localization and resection extent were classified as (1) Pure SFS group (PS group), (2) Associated SFS group (AS group), and (3) No SFS group (NS group). The general characteristics, neuroradiological findings, morbidity, pathology, and long-term seizure outcome after surgery were analyzed to extract the potential value of the surgery for SFS-related dysplasia. Results: Of 31 patients with FLE who underwent epilepsy surgery, 15 patients (9 males) were included PS group, 5 patients (5 males) in the AS group, and 11 patients (8 males) in the NS group. Eleven patients detected focal abnormal signals in the presurgical MRI. Six patients in the PS group demonstrated the suspected FCD in the SFS detected with MRI. All patients demonstrated focal abnormal hypometabolism foci in the PET-MR co-registration. 25 patients (80.6%) had been seizure-free since surgery, including all 15 patients (100%) of the PS group, 3 in 5 patients (60%) of the AS group, and 7 in 11 patients (63.6%) of the NS group. The difference in outcome between different groups was significant (p=0.004, PS vs. AS group; p=0.005, PS vs NS group). As of the last follow-up (mean 66.2±9.7months), 25 patients (80.6%) had been seizure-free since surgery (Engel’s class I). And antiseizure medication had been withdrawn in 19 patients (61.3%). Histologic examination of resected specimens revealed FCD in all 31 patients. The percentage of FCD II type was 100%, 60%, and 63.6% in three different groups respectively. Conclusion: SFS-related dysplasia is a neuropathologic entity with a favorable postoperative outcome. FCD II is the most common type of SFS-related dysplasia. FDG-PET co-registered with MRI should be performed in patients with suspected SFS-related dysplasia since it may depict areas of hypometabolism suggestive of dysplasia in the absence of MRI abnormalities.